Anthropology after Gluckman : the Manchester school, colonial and postcolonial transformations - Werbner, Richard P. (Manchester University Press, 2020)
This book places the Manchester School in the vanguard of modern social anthropology. Werbner reveals not only the cosmopolitan distinctiveness but also the force of creative difference in the ideas, interdisciplinary approaches, and travelling theories of the intimate circle around Max Gluckman.